Nizhny Novgorod's Legend about V. Korolenko: Myth and Context's Polyphony - Bachynska, Anastasiya (Pitannâ lìteraturoznavstva, 2013)
In the article the author researches social and communicative image of writer – the part of his literary identity. In the focus of attention are origin and features of functioning of Nizhny Novgorod's legend about Korolenko. The author analyzes perception of writer by both general population and literati, for example M. Gorky and S. Yeleonsky. At that time V. Korolenko published anticorruption article in local newspapers, as volunteer helped to fight hunger (1893) and he traveled across region of Nizhny Novgorod. In his literary work he reflected these activities. As well it was a reason, why peasants and the urban poor began to see a “mysterious prince” at him. We found several reasons of prince’s image appearance: 1) surname Korolenko sounds like “korolevich” (prince in Russian), 2) it correlates with actual philosophy of populism and 3) it reflects archetypal conception of just ruler, defending the truth and travelling incognito through his kingdom. As well V. Korolenko himself used the story of the prince errant. For example in the story “The blind musician” the main character Peter explored the world together with blind beggars and as a result he had got psychological transformation. F. Batyushkov the critic compared this scene with the Bible story of “Proud king Haggai”. So the author of this article showed and commented features of writer’s public perception within the framework of literary history and archetypical story. As a result we have an objective view of the perception of Korolenko by his contemporaries and the whole writer’s social role in 1880 – 1890's.